Comparative Effect of Cognitive-Perceptual Training on Cognitive Performance Across Playing Positions in Football - Gandhi Jomoh; Sambhu Prasad (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Football performance relies on cognitive-perceptual abilities that vary by playing position, yet evidence on position-specific cognitive-perceptual training is limited. This study investigated the comparative effect of cognitive-perceptual training on cognitive performance among university-level football players across different playing positions. Methods: Sixty male football players (18-25 years) were categorized as forwards (n = 20), midfielders (n = 20) and defenders (n = 20). Participants completed an eight-week cognitive–perceptual training program using the Vienna Test System. Reaction Speed, decision-making (Cognitrone) and Peripheral Perception were assessed using a pre–post design. Data were analyzed using mixed-design ANOVA. Result: A significant positional effect emerged for decision-making (F(2,57) = 5.17, p = .009, η² = .15), with midfielders exhibiting the greatest improvement. Conclusion: The findings suggest that cognitive-perceptual training effectively enhances key cognitive functions in football players, particularly decision-making among midfielders. Integrating such interventions into regular training may foster improved tactical and perceptual efficiency in competitive contexts.